2003
DOI: 10.1002/cm.10123
|View full text |Cite
|
Sign up to set email alerts
|

Genomic organization, alternative splicing, and expression of human and mouse N‐RAP, a nebulin‐related LIM protein of striated muscle

Abstract: Linkage analysis identifies 10q24-26 as a disease locus for dilated cardiomyopathy (DCM), a region including the N-RAP gene. N-RAP is a nebulin-like LIM protein that may mediate force transmission and myofibril assembly in cardiomyocytes. We describe the sequence, genomic structure, and expression of human N-RAP, as well as an initial screen to determine whether N-RAP mutations cause cardiomyopathy. Human expressed sequence tag databases were searched with the published 3,528-bp mouse N-RAP open reading frame … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
57
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 34 publications
(61 citation statements)
references
References 23 publications
4
57
0
Order By: Relevance
“…2A-C). We previously showed that N-RAP exon 12 is not expressed in adult hearts (Mohiddin et al, 2003). By using the exon 9 -14 primers, we observed a single PCR product from cardiac tissue between E10.5 and P21 that is consistent with omission of exon 12; the cardiac transcript in this region is 105 bases smaller than the predominant product from adult skeletal muscle, which includes exon 12 (Fig.…”
Section: Specificity Of N-rap Expressionmentioning
confidence: 64%
See 4 more Smart Citations
“…2A-C). We previously showed that N-RAP exon 12 is not expressed in adult hearts (Mohiddin et al, 2003). By using the exon 9 -14 primers, we observed a single PCR product from cardiac tissue between E10.5 and P21 that is consistent with omission of exon 12; the cardiac transcript in this region is 105 bases smaller than the predominant product from adult skeletal muscle, which includes exon 12 (Fig.…”
Section: Specificity Of N-rap Expressionmentioning
confidence: 64%
“…N-RAP is an actin-binding LIM protein that is concentrated at the ends of striated muscle cells (Luo et al, 1997;Zhang et al, 2001;Mohiddin et al, 2003). The N-RAP gene structure and coding sequence are highly conserved between mice and humans.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations